Strategi Pengembangan Agribisnis Peternakan Ayam Petelur di Kabupaten Tabanan - TRISNA KURNIAWAN, M. FAJAR; PUTRA DARMAWAN, DWI; SRI ASTITI, NW. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol. 1, No. 2, Oktober 2013, 2014)
Agribusiness is one sector which is based on farm business or the other fields that support it. Activity in the agribusiness sector includs any one or all of the chain along production, processing and marketing including poultry farm. This study aims to determine how the layer farmers profile, strategic internal factors (strengths and weaknesses) and external (opportunities and challenges) affecting farm poultry as well as the development of alternative strategies and what strategies are feasible priority. Respondents were termined using a proportional random sampling of layer farmers in Tabanan regency. Internal and external factors evaluated by the IFE matrix and EFE matrix. Alternative defined strategy with IE matrix and SWOT matrix, and for the determination of strategic priorities determined by matrix QSPM. The results showed that the internal factors are a major force in the development of poultry farm is a hereditary business and the availability of means of transport. Externally, the main factor being the availability of market opportunities and short distribution and population growth. Factors are the main challenges and the fluctuating price of chicken diseases. Main strategy (grand strategy) for poultry farm agribusiness development is market penetration and product development. Market penetration strategy is a strategy used to increase market share of the product or service through marketing efforts greater. Product development strategy is a strategy that aims to make companies that partnered to increase sales by improving or modifying existing products now. Alternative strategy is to increase market share to achieve the position of market leader through a policy of local governments and related enterprises, control and surveillance of pests or diseases of livestock farm in order to be sustainable, the capital guarantee and optimize field officers, and optimize working capital and increase ability in the development of an efficient agribusiness. Strategic priorities poultry farm agribusiness development is a strategy to achieve increased market share market leader position through policies of local governments and related companies.
Keywords: layer, agribusiness, internal-external factors, strategies